Advancing The Physical Education Program Of Bohol Island State University: A Blueprint For Enhancing Excellence (Journal of Namibian Studies : History Politics Culture, 2022)
In the dynamic realm of educational advancement, the commitment to excellence remains a steadfast cornerstone for institutions seeking to shape well-rounded individuals. At the heart of this pursuit lies the Physical Education program of Bohol Island State University (BISU), poised to transcend its current state and reach new heights of distinction. This thesis abstract embarks on a compelling exploration, delving into the intricate fabric of BISU's Physical Education program to unearth pathways for advancement. With an unwavering focus on excellence, this abstract sets out to dissect the program's core, dissecting its strengths, and identifying areas primed for refinement. Through a harmonious blend of meticulous analysis and visionary planning, the ultimate objective is to craft a comprehensive blueprint – a roadmap that resonates with BISU's resolute dedication to nurturing academic brilliance within its Physical Education program. As the academic landscape continues to evolve, this abstract stands as a beacon of proactive change, an embodiment of the institution's commitment to not just educate, but to elevate, transform, and inspire. The result of the study provides a thorough evaluation of teachers' and students' perceptions across key dimensions of the educational environment. It highlights shared viewpoints and nuanced distinctions that warrant attention. In the Faculty domain, consensus emerges in positive evaluations of adequacy, loading, professionalism, and performance. Both groups appreciate faculty dedication and competence, reflected in composite mean scores of 3.53 (teachers) and 3.76 (students). In Instruction, a divergence appears in teaching methods' assessment. Students rate these highly (3.73), while teachers are more critical (3.22). This suggests potential for pedagogical refinement or aligning strategies with student preferences. Regarding Student Services, contentment prevails in health, co-curricular activities, and classroom management. However, perceptions vary in sports and socio-cultural programs, where students are positive (3.56, 3.46) while teachers rate lower (3.25). The Library reveals a slight divergence: students rate utilization cautiously (3.60) compared to teachers (3.63), indicating room for enhancing engagement. For Physical Plant and Facilities, both teachers and students appreciate campus and classrooms. Yet, assembly and athletic facilities need improvement, marked by composite means of 2.97 (teachers) and 3.29 (students). The Overall Composite Mean confirms shared positive outlooks with scores of 3.44 (teachers) and 3.56 (students), reflecting an enriching educational experience. In essence, this analysis guides curriculum enhancement, resource allocation, and facility improvement for a holistic educational journey.